고혈압 환자의 비만관리를 위한 인터넷 기반 코칭 프로그램의 효과 - 전해옥(Jeon Hae Ok); 김옥수(Kim Oksoo) (Sŏngin Kanho Hakhoe chi, 2011)
Purpose: The purpose of this study was to investigate the effects of the internet based coaching program for obesity management on weight control related knowledge, self-efficacy, eating habits, physical activity and obesity related physiological indexes in hypertensive patients. Methods: The study design was non-equivalent control group pre-test-post-test design. A total of 43 subjects were overweight or obese hypertensive patients aged 30 or older, who were divided into experimental group (n=23) and control group (n=20). This program lasting 12 weeks consisted of a weight control related education, internet based individual coaching for diet, exercise and behavior modification, offering internet community and health counseling. The variables were measured three times (before the treatment, after 6 weeks, and after 12 weeks) and the collected data were analyzed by SPSS/WIN 17.0 program. Results: The experimental group had significantly improved weight control related knowledge, self efficacy, eating habits, body composition, and systolic blood pressure with time. Conclusion: The internet based coaching program was effective in improving obesity management, also this program will help to prevent cardiovascular disease of obese hypertensive patients.